The Role of Dermoscopy in Diagnosis of Benign Skin Neoplasms - Purnamasari, Indah; Sari, Maylita (Folia Medica Indonesiana, 2022)
Highlight: • Dermoscopy is a practical, non-invasive and accurate method for reducing the number of unnecessary excision of benign skin neoplasms. • Knowledge about vascular pattern and description setting can lead to a prompt benign skin neoplasm diagnosis. Abstract: Benign skin neoplasms are commonly found in the population. It has a well-differentiated and slow growth nature. The patients often come seeking treatment when the tumor has developed into malignancy. This usual delay in diagnosis and therapy frequently happens because early-stage mass has not generated any complaints by the patients. Detection and monitoring of benign skin neoplasms can be carried out earlier and more effectively if the clinician or dermatologist has the knowledge of distinguishing benign from malignant lesions. The histopathological examination can help to establish the diagnosis, but this method is invasive and requires an extended amount of time. Dermoscopy is a practical, non-invasive and accurate method for early detection of skin disorder which reduces the number of unnecessary excisions of benign skin neoplasms. Knowledge of the vascular pattern and arrangement description, combined with the additional dermoscopic feature can lead to the prompt diagnosis of benign skin neoplasms.